The effect of sitting position on sit-ski performance on a treadmill and in a ski ergometer - Cycle characteristics and physiological parameters: A case study - Sampolahti, V.; Linnamo, V.; Ohtonen, O. (10th International Congress on Science and Skiing, January 28 - February 1, 2025, Val di Fiemme, Italy, 2025)
INTRODUCTION: In sit-skiing, impaired athletes are classified into five classes based on the evaluations of their trunk control (LW10, LW10.5, LW11, LW11.5, LW12). A calculation system in which certain percentages are deducted of the competition finishing time (14.0%, 10.0%, 6.0%, 4.0%, 0.0%) has been created. [1] Two commonly used sitting positions are "kneeing" (KL) and "knee-high" (KH) positions [2]. Studies on biomechanical patterns and performance between classified athletes have mostly been conducted under laboratory conditions and have reported many positive patterns of KL for sit-skiing performance. [2,] In the ski ergometer, the effect of chancing sitting position in able-bodied athletes on performance in physiological and biomechanical parameters has been reported to be 7-15% favoring KL position [3]. The purpose of the present study wanted to measure the effect of sitting position on sit-skiing performance on a treadmill because it could simulate natural conditions better than in the ski ergometer.